Study guides

☆☆

Q: What is y 2 over 5 y 3 over 3?

Write your answer...

Submit

Still have questions?

Related questions

y/9 - 2/5 = 1/3 => y = 6 3/5 or 6.6

Of course. These are straight lines. Y = 5/2 Y = 2/5

1+4=5

Sin(2*pi/6) = sin(pi/3) which, by definition, is 0.5 If you wish, you can calculate y/1! - y^3/3! + y^5/5! - y^7/7! + ... where y = pi/3.

Slope = (y-5)/(3--6) = 1/3 y-5 = 1/3*9 y = 3+5 y = 8

Since we know the slope, m = 5/3, and the y-intercept 1/2, we arw able to write the equation of the line in the slope-intercept form, y = mx + b, so we have y = (5/3)x + 1/2.The standard form of the equation of the line is Ax + By = C.y = (5/3)x + 1/2y - y - 1/2 = (5/3)x - y + 1/2 - 1/2-1/2 = (5/3)x - y or(5/3)x - y = -1/2Thus, the standard form, Ax + By = C, of the equation of the line is (5/3)x - y = -1/2.

5

5/(2y) + 3 + 6/y + 2 = 31. Bring all the unknown (all terms containing a letter, here Y) to one side and known to the other5/(2y) + 6/y = 3 + (-3) + (-2)2. multiply all by 2, to get rid of it where it stands next to the y(2*5)/(2y) + (2*6)/y = 2*(-2)3. Multiply all :)5/y + 12/y = -44. add all the terms with unknows17/y = -45. Therefore, y=17/(-4)and y=-4.25To check, just substitute y=-4.25 into the starting equation 5/(2y) + 3 + 6/y + 2 = 3Another method with the same result:5/2y + 3 + 6/y + 2 = 35/2y + 6/y = 3 -3 -25/2y + 6/y = -2Multiply all terms by 2y in ordes to eliminate the fractions:5 + 12 = -4y17 = -4yDivide both sides by -4 to find the value of y:y = -4.25Check by substituting the value of y into the original equation which will work out as: 3 = 3

2x-y=5, y=2x-5 4x+y=4, y=4-4x 2x-5=4-4x 6x=9 x=3/2 y= 2(3/2)-5 y=-2

the Y in the sentence X plus Y equals 5 is Y=3 or 2 if the X is 2 or 3

(-x) + (-y) = -(x + y) Example: x = 2, y = 3 -2 + -3 = -5

1. x + y = 22. y = 2x - 13Rewriting 2. as:3. 2x - y = 13Adding 1 & 3 gives:4. 3x = 15x = 5Substituting x = 5 into 1. gives:5 + y = 2y = 2 - 5y = -3Checking values by substituting x = 5 and y = -3 into 2 gives:-3 = (2 * 5) - 13-3 = 10 - 13-3 = -3Therefore x = 5 and y = -3.

Y / 5 = .2 multiply both sides by 5 the answer is Y = 1

80 = 3 y + 2 y + 4 + 1 80 = 5 y + 5 80 - 5 = 5 y 75 = 5 y 15 = y So Y is 15

Substitute the values of (-6, 5) into the formula of: y-y1 = m(x-x1) y-5 = 1/3(x-(-6)) y-5 = 1/3x+2 y = 1/3x+7 So when x = 3 then y = 8

Of the points: (5, 3) (3, 0) (5, 2) and (0, 2) which means (x, y) thus the y values are 3, 0, 2 and 2 * * * * * True, but that does not answer the question that was asked. Only one of these points is on the y-axis and that is (0, 2).

the answer is -33/4 or -8.25

5 and 3 5+3 = 8 5-3 = 2 If you don't see and or don't want to just guess, then you might make this into a simple Algebra problem. x+y=8 x-y=2 The second equation is the same as x=2+y So 2+y+y=8 or 2y=6 and y=3, Finish by saying 3+x=8 so x=5

y= 1/2x - 2/3

y = -2/5

x/y = 5/(y^2) and y/x = 5/(x^2). So x/y + y/x = 5/(y^2) + 5/(x^2), which equals 5x^2/(x^2 y^2) + 5y^2/(x^2 y^2) equals 5(x^2 + y^2)/25 equals (x^2 + y^2)/5. x^2 = 25/y^2, so you get (25/y^2 + y^4/y^2)/5 equals ((25 + y^4)/y^2)/25, which shows that your math teacher is on crack. Seriously, I'm not sure that's true.

If: x -y = 2 then x = 2 +y If: x^2 -4y^2 = 5 then (2 +y)^2 -4y^2 -5 = 0 Removing brackets: 4 +4y +y^2 -4y^2 -5 = 0 Collecting like terms: 4y -3y^2 -1 = 0 Divide all terms by -3: y^2 -4/3y +1/3 = 0 Completing the square: (y -2/3)^2 -4/9 +1/3 = 0 => (y -2/3)^2 = 1/9 Square root both sides: y -2/3 = -1/3 or +1/3 Add 2/3 to both sides: y = 1/3 or 1 By substitution into original equation intersection are at: (7/3, 1/3) and (3, 1)

(2y-4)/(y+3)=(2-y-2)/(y+3) --> multiply both sides by (y+3) 2y-4=2-y-2 --> 2-2=0 (right hand side) 2y-4=-y --> add y to both sides 3y-4=0 --> add 4 to both sides 3y=4 --> divide both sides by 3 y=4/3

It is: 5/9x-y+2 = 0

If you mean y+3 = 2(x-1) then y = 2x-5